Memristive circuit-based model of central pattern generator to reproduce spinal neuronal activity in walking pattern - Masaev, Dinar N.; Suleimanova, Alina A.; Prudnikov, Nikita V.; Serenko, Mariia V.; Emelyanov, Andrey V.; Demin, Vyacheslav A.; Lavrov, Igor A.; Talanov, Max O.; Erokhin, Victor V. (Frontiers in Neuroscience, 2023)
Existing methods of neurorehabilitation include invasive or non-invasive stimulators that are usually simple digital generators with manually set parameters like pulse width, period, burst duration and frequency of stimulation series. An obvious lack of adaptation capability of stimulators, as well as poor biocompatibility and high power consumption of prosthetic devices highlights the need for medical usage of neuromorphic systems including memristors. The latter are electrical devices providing a wide range of complex synaptic functionality within a single element. In this work we propose the memristive schematic capable of self-learning according to bio-plausible spike-timing-dependant plasticity to organize the electrical activity of the walking pattern generated by the central pattern generator.